POSITIVE SILENCE TO THE REMOVAL OF TREES – AN ANALYSIS OF A LEGAL INSTITUTION - Haładyj, Anna; Kułak-Krzysiak, Katarzyna (Review of European and Comparative Law, 2019)
The authorisation for removing trees constituting a common nature protection instrument was supplemented in 2017 by the obligation to notify the intention to remove trees. The right to notify and object to the intention of tree removal corresponds conceptually to the model of positive silence provided for in the amended Code of Administrative Procedure as one of the ways of administrative silence. Our objective is to analyse procedural solutions and the substantive institution of environmental protection law which consists in a notification from the point of view of assessing the correctness of its application when considering law science and administrative proceedings